ChemInform Abstract: Oxidative Coupling of Methylamine with an Aminyl Radical: Direct Amidation Catalyzed by I2/TBHP with HCl. Issue 37 (16th September 2014) - Gao, Lingfeng; Tang, Haoming; Wang, Zhiyong
Abstract A series of disubstituted amides is prepared by an unprecedented iodine‐catalyzed oxidative coupling of arylmethylamines with N, N‐disubstituted formamides.